ANALISIS PENERIMAAN PAJAK HOTEL, PAJAK RESTORAN, PAJAK HIBURAN SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (Studi Pada Dinas Pendapatan Daerah Kota Malang) - PRASETIO PUTRI, RORO BELLA AYU WANDANI (Jurnal Mahasiswa Perpajakan, 2015)
The Local Genuine Income (PAD) is a source of local income which may consist of local tax, local retribution, separated local wealth management, and others. Hotel Tax, Restaurant Tax and Entertainment Tax are local tax components. Hotel, restaurant and entertainment are a potential sector for the improvement of local revenue. The objective of research is to understand the contribution, effectiveness and growth rates of hotel, restaurant and entertainment taxes to local tax and Local Genuine Income. It is expected that research will provide benefit and input for the local government of Malang City, especially to the Official of Local Income. Research method is descriptive. Data are secondary which obtain from The Report of Target and Realization of Local Income Revenue from the Period 2006-2013 made by The Official of Local Income. The Result of research indicates that hotel, restaurant and entertainment taxes in Malang City have quite great potential compared to other tax types. It is consistent to research objective which is to analyze and to explain the contribution, effectiveness and growth rates of hotel, restaurant and entertainment taxes to Local Genuine Income. The average contribution rate of hotel tax to Local Genuine Income is 5.81%, while those of restaurant tax and entertainment tax are 10.36 % and 1.77 %. The average effectiveness rate of hotel tax is 106.94 %, while those of restaurant tax and entertainment tax are 105.31 % and 113.74 %. The growth rates of hotel, restaurant and entertainment taxes are 22.77 %, 11.11 % and 21.54 %. Keywords: Local Genuine Income, Local Tax, Hotel Tax, Entertainment Tax, Restaurant Tax, Contribution, Effectiveness, Growth Rate